3+2x=7x-47

Simple and best practice solution for 3+2x=7x-47 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3+2x=7x-47 equation:


Simplifying
3 + 2x = 7x + -47

Reorder the terms:
3 + 2x = -47 + 7x

Solving
3 + 2x = -47 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
3 + 2x + -7x = -47 + 7x + -7x

Combine like terms: 2x + -7x = -5x
3 + -5x = -47 + 7x + -7x

Combine like terms: 7x + -7x = 0
3 + -5x = -47 + 0
3 + -5x = -47

Add '-3' to each side of the equation.
3 + -3 + -5x = -47 + -3

Combine like terms: 3 + -3 = 0
0 + -5x = -47 + -3
-5x = -47 + -3

Combine like terms: -47 + -3 = -50
-5x = -50

Divide each side by '-5'.
x = 10

Simplifying
x = 10

See similar equations:

| 7-4(3x-5)=9-3(2x-1) | | 2x^2+10x=180 | | 14.2-d=9.2 | | 2.9(f+4)-1.22=16.18 | | -2.12(w+-4)=12.72 | | -4r^2+21r=r+13 | | 45=6x+3x+9 | | 140/u=28 | | 4x^2-1/16=0 | | 11(y-881)+234=806 | | R=8x^2+2x-9 | | 17+2= | | 4x^2-1/6=0 | | 6.7-j=6.8 | | 9x-3=6x+5 | | X^2+1=4+2x-x^2 | | M/5+(3m-6)/2=2m-6 | | 2.8(t-6)+1=9.4 | | 3(s+1.78)=11.67 | | 183-p=851 | | ((24x)/(884-24x))=1 | | 10(b+235)=760 | | 3g+6=18 | | 0=a^2-20a+96 | | A^2-20a=96 | | 4(h-554)=896 | | 31-3(x+1)=3x | | ((2p)/(p+6))=1 | | -7(u+-5)=-56 | | 5x+10=8x+4 | | 42+7k=21 | | -3.28=2(1.5y-.5) |

Equations solver categories